A Comparison of the Effects of Sevoflurane, Propofol, and Propofol Combined with Butorphanol in Suppressing Sufentanil-Induced cough—A Randomized Controlled Trial - Ji H; Zhang F; Yang M; Xu X; Sun Y; Xia X; Li Y (Drug Design, Development and Therapy)
Haoyu Ji,1,* Fazhong Zhang,2,* Ming Yang,1 Xiaomei Xu,1 Yuanming Sun,1 Xiaoqiong Xia,1,* Yuanhai Li2 1Anesthesiology Department, Chaohu Hospital Affiliated with Anhui Medical University, ChaoHu, Hefei, People’s Republic of China; 2Anesthesiology Department, The First Affiliated Hospital of AnHui Medical University HeFei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoqiong Xia, Anhui Province. Anesthesiology Department, Chaohu Hospital Affiliated with Anhui Medical University, ChaoHu, HeFei, 238000, People’s Republic of China, Tel +8613966386669, Email xxq2366833@sina.com Yuanhai Li, Anesthesiology Department, The First Affiliated Hospital of AnHui Medical University HeFei, HeFei, 230000, People’s Republic of China, Tel +861350569756, Email liyuanhai-1@163.comObjective: To study the safety and efficacy of sevoflurane pretreatment in preventing sufentanil-induced cough in children and to compare its antitussive effect with that of butorphanol, an opioid analgesic that has been proven effective in clinical trials.Data and Methods: This was a prospective randomized controlled trial. A total of 174 patients who underwent ENT surgery at Chaohu Hospital Affiliated with Anhui Medical University were enrolled and divided into groups S, C and B, with 58 patients in each group, according to the random number table method. General anesthesia was induced with 5% sevoflurane in Group S, 2.5 mg/kg of propofol and 30 μg/kg of butorphanol in Group B, and 2.5 mg/kg of propofol and 1 mL of normal saline in Group C. The cough grade, intraoperative hemodynamic data, blood oxygen saturation, and adverse reactions within 24 h after the operation were recorded.Results: The overall cough grade significantly differed among the 3 groups (P< 0.05). Compared with those of Group C, the cough grades of Groups S and B were significantly lower (P< 0.05). There was no significant difference in the cough grade between Group S and Group B (P> 0.05). Groups S and B cannot be considered equivalent. There were no significant differences in the MAP, HR, SpO2 or BIS value among the three groups at different time points (P> 0.05). There was no significant difference in the incidence of postoperative nausea, vomiting, dizziness or chills among the 3 groups (P> 0.05).Conclusion: Induction of anesthesia using 5% sevoflurane to reduce Bis to 60 in children significantly reduces the probability of sufentanil-induced coughing (SIC) without significant hemodynamic fluctuations.Plain Language Summary: When sufentanil is used to induce anesthesia without intervention, there is a high probability of a cough reaction (64.7%), which is the first in a series of complications that can occur during the anesthesia induction period, such as an increased intraocular pressure and an increased intracranial pressure. This condition is called sufentanil-induced coughing (SIC).There are several ways to suppress SIC. However, there are few studies on pediatric SIC, and the drugs most commonly used to prevent SIC require intravenous access establishment; thus, it is not suitable for children. The aim of this study is to investigate the efficacy of sevoflurane, one of the most commonly used anesthetic drugs in children, in preventing SIC.In this study, the efficacy of sevoflurane in suppressing SIC was compared with that of butorphanol, an opioid analgesic that have been proven effective in clinical trials, by comparing the clinical data of the group of patients who underwent general anesthesia induction with 5% sevoflurane with those of a blank control group. Finally, reducing the BIS value to 60 with 5% sevoflurane effectively prevented SIC while maintaining hemodynamic stability.Our results can be used as the basis for the increased use of sevoflurane and for further exploration of its efficacy and safety.Keywords: pediatric surgery, ears, nose, and throat surgery, general anesthesia, sevoflurane, butorphanol